Conservation of the Richmond Birdwing Butterfly in Australia - Sands, Donald P.A; New, Tim R. (Springer Netherlands : Imprint: Springer, 2013)
This survey of one the longest insect conservation campaigns in Australia deals with one of the most iconic endemic  papilionid butterflies, the Richmond birdwing (Ornithoptera richmondia), threatened by clearance and fragmentation of subtropical rainforest in eastern Australia and the spread of an alien and poisonous larval food-plant. It was thus lost from much of its former range during the twentieth century. Its conservation has involved many aspects of community involvement, developed over more than 20 years, and its recovery has focused on habitat restoration and weed eradication, in conjunction with conservation of remaining forest fragments. The work involved the entire historical range of the butterfly, and has emphasised landscape connectivity, enhanced through extensive plantings of native food plants. Interest has been maintained through extensive publicity, community education and media activity, and the programme has provided many lessons for advancing insect conservation practice in the region.  This summary of the extensive scientific and public aspects of this innovative insect conservation study, emphasises the many different factors that can influence community interest and practical outcomes.